EXAMINING LIBRARY PROFESSIONALS’ METHODS OF SOFT SKILLS LEARNING: A CASE OF LIBRARY PROFESSIONALS WORKING IN PRIVATE SECTOR UNIVERSITIES OF PAKISTAN - Muhammad Ismail (PhD) , Sajjad Ahmad (PhD) , Muhammad Idrees; M. Haseeb (PhD) (IJoLIS, 2025)
Purpose: The purpose of this research study is to examine the methods of soft skill learning by library professionals working in private sector universities in Pakistan. Design/Methodology/Approach: The study used quantitative research design based on a questionnaire. The target Population of the study included all 474 library professionals working in the private sector universities in Pakistan. To get relevant data, non-probability convenience sampling technique was used deployed to 340 library professionals out of which 270 useable questionnaires were received back dully filled in. Both descriptive and inferential statistics were used for data analysis using SPSS-21. Research limitations: The study is limited to the responses collected from library professionals working in the private sector university libraries only. Originality value: This is the first study in Pakistan that dealt with the preferred methods of soft skills learning of library professionals by using a large group (N = 474) of university library professionals. Key findings: Findings of the study revealed that library professionals working in private sector universities preferred to learn soft skills from experts and colleagues. Overall results indicated that from library professionals’ perspective, soft skills should be taught to them using face-to-face methods. Practical implications: The study will encourage researchers in Pakistan and elsewhere to analyse soft skills of library professionals of various type of libraries and to frame practical training modules for librarians to inculcate in them the modern methods of soft skills to deal with a varied kind of readers. Contribution to knowledge: It is one of the first ever studies on the subject as only a few studies have been conducted in Pakistan measuring the soft skills of library professionals of private sector universities of Pakistan.